2018
DOI: 10.1177/0194599818756829
|View full text |Cite
|
Sign up to set email alerts
|

Ménière's Disease Pathophysiology: Endolymphatic Sac Immunohistochemical Study of Aquaporin‐2, V2R Vasopressin Receptor, NKCC2, and TRPV4

Abstract: Objectives Endolymphatic sac (ELS) pathophysiology in Ménière's disease (MD) remains poorly understood. We identified from the literature a group of proteins expressed on the ELS and involved in endolymph volume regulation: aquaporin-2 (AQP2), vasopressin receptor V2R, sodium potassium chloride cotransporter 2 (NKCC2), and transient receptor potential cation channel V4 (TRPV4). Our objective was to determine whether their ELS expression was altered in MD, to better understand the pathophysiology of endolymphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
(98 reference statements)
0
18
0
Order By: Relevance
“…Nordström et al found that 40% of human endolymphatic sac epithelial cells express Na + -K + -ATPase, indicating that they have considerable secretory ability ( 12 ). Immunohistochemical and ultrastructural studies showed that the endolymphatic sac of MD patients had excessive secretion of glycoprotein ( 13 , 14 ), and the overexpression of aquaporin-2 in the endolymphatic sac epithelium was also involved in the formation of endolymphatic hydrops ( 15 ), suggesting that the endolymphatic sac secretion exceeded absorption, increasing the inner ear pressure. Li et al used micro-computed tomography and high-resolution synchrotron phase contrast non-invasive imaging techniques to image and analyze the structures of the utricular duct and utricular-endolymphatic valve (or Bast's valve) of the human temporal bone specimens, suggesting that there is a two-way exchange of endolymphatic fluid involving the utricle, semicircular canal, and endolymphatic duct.…”
Section: Discussionmentioning
confidence: 99%
“…Nordström et al found that 40% of human endolymphatic sac epithelial cells express Na + -K + -ATPase, indicating that they have considerable secretory ability ( 12 ). Immunohistochemical and ultrastructural studies showed that the endolymphatic sac of MD patients had excessive secretion of glycoprotein ( 13 , 14 ), and the overexpression of aquaporin-2 in the endolymphatic sac epithelium was also involved in the formation of endolymphatic hydrops ( 15 ), suggesting that the endolymphatic sac secretion exceeded absorption, increasing the inner ear pressure. Li et al used micro-computed tomography and high-resolution synchrotron phase contrast non-invasive imaging techniques to image and analyze the structures of the utricular duct and utricular-endolymphatic valve (or Bast's valve) of the human temporal bone specimens, suggesting that there is a two-way exchange of endolymphatic fluid involving the utricle, semicircular canal, and endolymphatic duct.…”
Section: Discussionmentioning
confidence: 99%
“…The increased hydrops was detected in 3 patients, 2 of which exhibited concomitant symptomatic worsening, suggesting that EDB does not always work to improve EH in MD. As a high degree of interindividual variability exists in the etiology of MD (11,39), it was speculated that two etiologically distinct inner ear pathologies (hypersecretion and malabsorption of endolymph) may exist in the sacs of different patients with MD and thus not all MD patients will benefit from EDB.…”
Section: Discussionmentioning
confidence: 99%
“…This simply highlights the complexity of this disease and reveals the ongoing needs for further study in optimal treatment options for MD. An immunohistochemical and ultrastructural investigation of the human endolymphatic sac in MD revealed both the secretion of glycoproteins and the possible existence of hypersecretions of endolymph in the sac (8)(9)(10), and an increased expression of aquaporin-2 in the endolymphatic sac epithelium of patients with MD was proposed to be involved in the pathophysiology of EH (11), which may support the assumption that an increased secretion outweighs a decreased absorption resulting in increased pressure in the inner ear (12). According to this hypothesis, a novel surgical sac technique, endolymphatic duct blockage (EDB), was proposed for the treatment of MD and shown be effective for the control of symptoms of MD, without any noticeable cochlear and vestibular damage (12).…”
Section: Introductionmentioning
confidence: 99%
“…Of these genes, evidence of decreased expression in MD has been noted for Atp13a5, Cacna2d1, and Ank2 (23) while Cav1 expression has been shown to be increased in patients with MD (23,31). While it has been suggested that TRPV4 expression may be decreased in human endolymphatic sac tissue from MD patients (82), a subsequent case-control replication study examining TRPV4 expression failed to demonstrate an association between TRPV4 expression and MD (83). Expression of TRPV4 in the cochlea in patients with MD has not been compared to unaffected human patients.…”
Section: Implications For Mechanisms Underlying Meniere's Diseasementioning
confidence: 99%